Comparison of open-source cloud management platforms: OpenStack and OpenNebula - Xiaolong Wen; Genqiang Gu; Qingchun Li; Yun Gao; Xuejie Zhang (2012 9th International Conference on Fuzzy Systems and Knowledge Discovery, 2012)
Cloud management platforms may manage the resources provided by the infrastructure as a service (IaaS) cloud. With the rapid development of open-source cloud platforms, they have been widely used due to open and free, some of them can substitute commercial clouds. Some existed related works only concisely compare the basic features of open-source platforms, and not including some new released features. In this paper, we firstly present the function of OpenStack and OpenNebula briefly, and then compare them from provenance, architecture, hypervisors, security and other angles in detail. Moreover, we provide some deployment recommendations according to different user demands and platform characteristics.